On the ridges, undulations, and streams in Gaia DR2: linking the topography of phase space to the orbital structure of an N-body bar - Fragkoudi, Francesca; Sormani, Mattia C. (Monthly notices of the Royal Astronomical Society, 2019)
We explore the origin of phase-space substructures revealed by the second Gaia data release in the disc of the Milky Way, such as the ridges in the Vϕ–r plane, the undulations in the Vϕ–r–Vr space and the streams in the Vϕ–Vr plane. We use a collisionless N-body simulation with cospatial thin and thick discs, along with orbit integration, to study the orbital structure close to the Outer Lindblad Resonance (OLR) of the bar. We find that a prominent, long-lived ridge is formed in the Vϕ–r plane due to the OLR which translates to streams in the Vϕ–Vr plane and examine which closed periodic and trapped librating orbits are responsible for these features. We find that orbits which carry out small librations around the x1(1) family are preferentially found at negative Vr, giving rise to a ‘horn’-like feature, while orbits with larger libration amplitudes, trapped around the x1(2) and x1(1) families, constitute the positive Vr substructure, i.e. the Hercules-like feature. This changing libration amplitude of orbits will translate to a changing ratio of thin/thick disc stars, which could have implications on the metallicity distribution in this plane. We find that a scenario in which the Sun is placed close to the OLR gives rise to a strong asymmetry in Vr in the Vϕ–Vr plane (i.e. Hercules versus ‘the horn’) and subsequently to undulations in the Vϕ–r–Vr space. We also explore a scenario in which the Sun is placed closer to the bar corotation and find that the bar perturbation alone cannot give rise to these features.
Gesehen am 10.10.2019